Novel biocompatible silver nanoparticles for controlling the growth of lactic acid bacteria and acetic acid bacteria in wines. (April 2015) - García-Ruiz, A.; Crespo, J.; López-de-Luzuriaga, J.M.; Olmos, M.E.; Monge, M.; Rodríguez-Álfaro, M.P.; Martín-Álvarez, P.J.; Bartolome, B.; Moreno-Arribas, M.V.
Abstract: This paper reports the inhibitory potential of two new silver-based biocompatible nanoparticles (Ag NPs), specifically synthesized for this study, against Gram-negative and Gram-positive bacteria, such as Escherichia coli and Staphylococcus aureus, and different wine lactic acid bacteria (LAB) ( Oenococcus oeni, Lactobacillus casei, Lactobacillus plantarum and Pediococcus pentosaceus ) and acetic acid bacteria (AAB) ( Acetobacter aceti and Gluconobacter oxydans ). Both solid nanoparticles, dried PEG-Ag NPs1 (20.01% silver content) and glutathione-stabilized GSH-Ag NPs2 solution (0.197 mg/mL silver content), showed homogeneous size distribution and physicochemical properties compatible with their use as antimicrobial agents. The nanoparticles showed different antimicrobial spectra, with PEG-Ag NPs1 being more effective (lower IC50 values) against Gram-negative strains, whereas GSH-Ag NPs2 showed similar efficiency against Gram-negative and Gram-positive strains, with the exception of O. oeni strains, which turned out to be notably susceptible to them (IC50 ∼1 μg/mL, Ag concentration). For the LAB and AAB tested, these nanoparticles showed IC50 values (particle concentration) of the same order as those for the widely used additive potassium metabisulphite, at least as calculated for PEG-Ag NPs1 . These results confirm the potential of Ag NPs in controlling microbial processes in winemaking, and open new investigations on the design and use of antimicrobial-specific silver-based nanoparticles in oenology. Highlights: New silver nanoparticles (NNPs) stabilized with biocompatible materials were synthesized. NNPs showed different antimicrobial spectra, against Gram-negative and Gram-positive. For wine bacteria, NNPs showed IC50 values close to those of the current additive SO2 . Glutathione-stabilized silver NNP was extraordinarily effective against O. oeni . NNPs size and surface state are important for the antimicrobial activity.